An Evaluation of the Courses in Curriculum of Undergraduate Preschool Teacher Training by Instructors in General Perspective - Nilay DEREOBALI; Gülsen ÜNVER (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Preschool education is of considerable importance for individual and social development. Therefore, qualified preschool teacher training is needed. The present study evaluates the Curriculum of Undergraduate Preschool Teacher Training (CUPTT), which was initiated in the academic year 2006, on the basis of instructors’ opinions. The data were collected with a questionnaire from 65 instructors employed in the Undergraduate Programs for Preschool Teacher Training in 26 universities in Turkey. Most of the instructors in the study stated that the courses in the curriculum are appropriate. In addition, they suggested adding 70 courses and changing the titles of 30 courses. There is a tendency to use the term ‘preschool education’ in these courses. The results of the study could promote detailed analyses on the Curriculum of Undergraduate Preschool Teacher Training in terms of its administration and implementation and serve as a reference for prospective curricula and their evaluation.